Utilization Of Semantic Values And Local Community Metaphor In Creating Furniture Identity - Alexander, Sigau; Musdi, Shanat (International Journal of Scientific & Technology Research, 2020)
Investigating furniture metaphor and identity are challenging because the metaphors are mostly deliberated in the context of language. This paper explores how the extent to which a source represents the meaning a designer intends to convey and is related to a target affect the selection of that source. By providing a thorough analysis of metaphor’s characteristics and express meanings to users via furniture form and appearance, systematic research survey was employed to obtain the first-hand data in presenting identity of Sarawak in furniture design that focus on local content of Dayak and Orang Ulu’s of Sarawak. Findings of the studies and provisional results are discussed from a theoretical and practical point of view, and recommendations for generating successful furniture design according to popular metaphors. The researchers believe, by embedding the semantic values and mapping local identity metaphor in the product aesthetics increase consumers desire to pay furniture items with high value for quality products rather than buying products at low prices. In conclusion, this paper aims to identify Sarawak’s local identity that potential to be a design elements of furniture design; Finally, this research intentions to analyze, identify and apply biomimicry of Sarawak local’s identity that able to symbolize furniture of Sarawak.